Exploratory study: the impact of implementing “you and me” sexual education program in the family - Dita Permata Aditya; Adhitya Riska Yunita; Inga Markiewicz; Ellya Rakhmawati (Universitas Ahmad Dahlan, 2022)
In recent years, there was news about sexual violence experienced in early childhood. Sexual violence becomes public health issue in many countries, which has negative consequences for the victims. The impact of sexual violence can affect children psychologically, physically, psychosocially, and etc. The study aims to determine the impact of implementing the sexual education “You and Me” program in the family. Rutgers WPF and PKBI Central Java have provided the “You and Me” program since 2017, but the several schools have adjusted the implementation of sexual education based on the learning theme. This study used the qualitative descriptive approach method. The research subjects consist of 5 participants of parents who have children at the age of 2-6. Data analysis techniques are carried out into four stages: data reduction, descriptive data presentation, data classification or coding categorization, and concluding. The result stated that the impact of the sexual education “You and Me” program on children has various effects and aligns with sexual education. Therefore, it can be concluded that the application of sexual education from five participants is quite effective. The results showed that the participants had a positive impact on children's behavior and thoughts while delivering sexual education. Although not all participants told their experiences in applying sexual education, most of them showed the positive impact of the children’s behaviour and thoughts.